The Private Cosmology of Public Disgust. (2nd September 2021) - Springer, Michael
Abstract: Alongside the public and private, the sacred can represent a third social-political dispensation, as Raymond Geuss notes. The modern liberal public/private divide represents a historical anomaly, with the sacred putatively consigned to the private realm. However, recent empirical research into disgust and its influences on moral psychology casts doubt on the extent to which such schemes have in fact removed phenomena connected with the sacred from the public realm. In this paper, I argue for the continuity between disgust and the idea of ritual pollution, demonstrating how an understanding of the moral psychology of the latter phenomenon helps account for certain aspects of our ostensibly secular public realm. Of these aspects, I focus primarily on racism, and specifically individuals' avowals of disgust in response to racism in the contemporary USA and UK. I argue that the idea of ritual pollution shows that such a response indicates a number of potential drawbacks to the socio-moral scheme underpinning the disgust, which in turn have the potential to limit social efforts to eradicate racism. I conclude that such socio-moral disgust is itself morally questionable in important ways, in addition to having the aforementioned instrumental shortcomings.